Impact of Employee Engagement on Performance at A Pump Supplier - Stephen Bale; Alan Pillay (International Journal of Multi Discipline Science, 2021)
The study aimed to investigate the impact of employee engagement on performance at a South African pump supplier. The research adopted a qualitative study and a non-probability purposeful sampling technique with a target population of ten employees at the company. It examined the factors that contributed to the development of employees’ engagement and the effect of engagement on employee performance. The research instrument used interview and was analyzed qualitatively. Key findings revealed that the employees at the company are disengaged due to ineffective leadership, poor communication between management and employees, lack of a recognition system, inadequate employee participation in decision-making, and an absence of a strategic and coordinated approach to the employees’ well-being. Recommendations were that the organization should allow its workforce to provide input in the decision-making of the organization, improve effective and transparent internal communication, employee development and empowerment, and an effective recognition system. Leaders should support the effective utilization of employee skills and capabilities. The study showed that there is a relationship between employee engagement and performance due to the lack of employee engagement that lowered employee capability and affected the organization's bottom line. Designing and implementing an effective employee engagement strategy is, therefore, desirable to the employee and organizational performance.